2019
DOI: 10.3390/pharmaceutics11090440
|View full text |Cite
|
Sign up to set email alerts
|

Impact of GSTA1 Polymorphisms on Busulfan Oral Clearance in Adult Patients Undergoing Hematopoietic Stem Cell Transplantation

Abstract: Background: Busulfan pharmacokinetics exhibit large inter-subject variability. Our objective was to evaluate the influence of glutathione S-transferase A1 (GSTA1) gene variants on busulfan oral clearance (CLo) in a population of patients undergoing hematopoietic stem cell transplantation. Methods: This is a quasi-experimental retrospective study in adult patients (n = 87 included in the final analyses) receiving oral busulfan. Pharmacokinetics data (area under the plasma concentration-time curve (AUC) determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
5
12
0
Order By: Relevance
“…For example, Abbasi et al 14 stated that GSTA1 was not significant influence factor of intravenous (IV) Bu clearance. However, Michaud et al 15 reported that adult patients carrying GSTA1 loss of function *B allele were at increased risk of overdosing on their initial busulfan oral dose. Yin et al 16 stated adult patients with the GSTA1 *A/*B genotype had a significantly higher AUC, higher peak concentration (C max ) and lower clearance (CL).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Abbasi et al 14 stated that GSTA1 was not significant influence factor of intravenous (IV) Bu clearance. However, Michaud et al 15 reported that adult patients carrying GSTA1 loss of function *B allele were at increased risk of overdosing on their initial busulfan oral dose. Yin et al 16 stated adult patients with the GSTA1 *A/*B genotype had a significantly higher AUC, higher peak concentration (C max ) and lower clearance (CL).…”
Section: Introductionmentioning
confidence: 99%
“…More clarification is needed to establish a thorough understanding of the role played by CYP39A1. In adults, many authors confirmed the impacts of GSTA1 in Asians and Caucasians (Supplementary Table S1), such as Kim et al in Koreans [30], Terakura et al in Japanese [14], and Michaud et al in Canadians [40].…”
Section: Discussionmentioning
confidence: 78%
“…A similar pattern was observed in urine, with EXE-cys, DHE-cys, and DHE-Gluc comprising 63%, 19%, and 16% of the total EXE metabolites, respectively. (34,35) and in Hardy Weinberg equilibrium. GSTM1 genotyping results indicated that 42 subjects exhibited the GSTM1 null genotype (62%), 18 subjects had one copy of GSTM1 (26%), while only 6 subjects had both copies present (9%).…”
Section: Table 1 Rate Of Exe-gsmentioning
confidence: 99%
“…The GSTA1*B allele has been linked to lower hepatic expression of GSTA1 and altered metabolism of certain medications (32,33). In the Caucasian population, the GSTA1*B allele has a minor allele frequency (MAF) of 0.43-0.49 (34,35). Additionally, a polymorphic whole-gene deletion of GSTM1 has been identi ed (MAF of 0.48-0.57 in Caucasian populations) (36).…”
mentioning
confidence: 99%